Design of ballasted railway track foundations under cyclic loading - Shahin, Mohamed (American Society of Civil Engineers, 2009)
The foundations of ballasted railway tracks are usually consisted of a graded layer of granular media of ballast placed above a naturally deposited subgrade. Available methods for design of track foundations are based on determination of an adequate granular layer thickness of ballast so that subgrade shear failures and plastic deformations produced by the transmission of imposed train loads are prevented. However, the deformation of ballast itself is ignored in almost all available design methods. In addition, most available methods do not represent true cyclic loading situations and rather provide oversimplified solutions based on static loading conditions. In this paper, a method that can be used to calculate the deformation of ballast under train cyclic loading is presented. The method is deemed to complement the existing methods of design of ballasted railway track foundations.